-10=-8+6x-2

Simple and best practice solution for -10=-8+6x-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -10=-8+6x-2 equation:


Simplifying
-10 = -8 + 6x + -2

Reorder the terms:
-10 = -8 + -2 + 6x

Combine like terms: -8 + -2 = -10
-10 = -10 + 6x

Add '10' to each side of the equation.
-10 + 10 = -10 + 10 + 6x

Combine like terms: -10 + 10 = 0
0 = -10 + 10 + 6x

Combine like terms: -10 + 10 = 0
0 = 0 + 6x
0 = 6x

Solving
0 = 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
0 + -6x = 6x + -6x
Remove the zero:
-6x = 6x + -6x

Combine like terms: 6x + -6x = 0
-6x = 0

Divide each side by '-6'.
x = 0

Simplifying
x = 0

See similar equations:

| 4-3x=-3x+6 | | f(3)=-2(3)+5 | | 9x+3=17x | | 21x-26=23x-9 | | -5(1+6n)=10 | | -3(3s-3)-9=-2(8s+6)-2 | | Y+20=10(x+9) | | 6x-256=2 | | -4x^2+x-3=0 | | .90x+0.05(6-x)=0.10(71) | | 10n+100-10=600 | | 7x^2+12x=y^2 | | (8/9)×(6/7)= | | 500x+800y=11500 | | .36(18)+.06x=0.12(24+x) | | -24n^10+3n=0 | | 8-3(x-4)=2x+5 | | 22-5x=2x-13 | | 15x-15=-12x | | (8/9)×(6/7) | | v/4-2.1=-8.5 | | 2/3x-2/3 | | 1.5=-7w+12.7 | | 3+2x+2=3x+4 | | -7=-5x-2x+7 | | 28+3n=34 | | -7(8-3k)+3k=-224 | | 7/9-8/9 | | 4/9-2/5c=4 | | 500=22.7x+304 | | 22x-38=12x-98 | | 1100+800+4x=700+300+7x |

Equations solver categories